Application of ohe Total Aproximation Method for the Investigation of the Temperature Regime of a Polychromatic Solid-State Lamp - Dabulytė, J.; Ivanauskas, F. (Nonlinear Analysis: Modelling and Control, 2005)
In this paper the application of the total approximation method for polychromatic solid-state lamp was considered. The main goal of this work was to present an investigation method for the temperature regime of n LEDs based on the investigation of the temperature regime of one LED. There were presented numerical results of the investigated problem.
Keywords: light-emitting diode; lighting source; temperature regime; total approximation method